Can we Identify the Fed's Preferences? - Jean-Bernard Chatelain; Kirsten Ralf (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Durbin (1970) pre-tests of Ramsey optimal policy versus time-consistent policy rejects time-consistent policy and optimal simple rule for the U.S. Fed during 1960 to 2006, assuming the reference new-Keynesian Phillips curve transmission mechanism with auto-correlated cost-push shock, including or not working capital. Estimates of a structural VAR shows that Ramsey optimal policy models the persistence of inflation, output gap and federal funds rate without requiring two additional parameters for inflation indexation and habit persistence. The number of reduced form parameters is larger with Ramsey optimal policy than with time-consistent policy although the number of structural parameters, including central bank preferences, is the same. The new-Keynesian Phillips curve model is under-identified with Ramsey optimal policy (one identifying equation missing) and hence under-identified for time-consistent policy (three identifying equations missing).
Additional information: Updated version: August 26, 2017
Keywords: C61; C62; E31; E52; E58; 330; Ramsey optimal policy; Time consistent policy; Identification; Central bank preferences; New-Keynesian Phillips curve